Push-out Bond Strength of Two Types of Dental Post Luted with Two Types of Cement at Two Different Root Levels - Mohammed Nasser Alhajj; Nurul Shafiqah Salim; Yanti Johari; Mohamad Syahrizal; Nor Aidaniza Abdul-Muttlib; Zaihan Ariffin (University of Zagreb. School of Dental Medicine, 2020)
Objective: Endodontically treated teeth may require posts for retaining the core and replacing the coronal structures that have been lost. The of this study was to evaluate and compare the push-out bond strength between different types of post cemented with different types of luting ce-ment at different types of root level. Material and Methods:In this in-vitro study, a total of 48 single-rooted permanent human teeth were decoronated, and the roots were treated endodontically. Fol-lowing post space preparation, the sample was divided into four groups (n= 12 each) based on the types of post and cement. Two different types of post [GC everStick ® POST (ES) and Parapost ® Fiber Lux TM (PF)], and two different types of cement [G-CEM TM (G), and RelyX TM (R)] were used according to the manufacturer's instructions. All roots were sectioned at the coronal and middle thirds with a thickness of 3±0.1mm. The Push-out bond strength (PBS) test was performed using a universal testing machine at a cross-head speed of 0.5mm/ min. The bond strength values were recorded, and the data were analyzed using the SPSS program. Apart from descriptive statistics, three- ANOVA was used for the interaction of the independent variables (post, cement, and root level). For differences between the groups, the Mann-Whitney U test was used. A P-value of less than 0.05 was considered significant for all analyses. Results: Push-out bond strength of samples at the middle level (11.38±10.31 MPa), with PF posts (11.18±9.98 MPa) and of those luted with RelyX TM Unicem cement (13.26±8.73 MPa) was higher than that of their counterparts. The PBS means of RelyX TM Unicem cement at both root levels were much higher than PBS means of G-CEM TM cement. Three-way ANOVA test revealed a significant effect for each variable with a higher effect of cement (Sum of Squares= 1310.690; P< 0.001). No significant difference (P= 0.153) was found between the coronal and middle parts and between ES and PF posts (P= 0.058). However, a highly significant difference (P< 0.001) was found between RelyX TM Unicem and G-CEM TM cements. Conclusion: The type of cement had a significant effect on push-out bond strength with RelyX TMUnicem which had higher values than G-CEM TM. However, the type of post and root level had no significant effect on PBS, although Parapost® Fiber Lux TM and middle root level had higher values than their counterparts.